Relation of Religiosity and Multiculturalism with Student Tolerance in East Java - Reza Ahmad Zahid; A. Jauhar Fuad; Ali Imron (Islamica: Jurnal Studi Keislaman, 2022)
Tolerance is an important issue in the life of the nation and state, and is related to religiosity and multiculturalism. Theoretically, an open religious attitude tends to make people tolerant and a closed religious attitude tends to make people intolerant. This study uses a quantitative research design, and data collection technique employs a questionnaire with google form. The analysis used is descriptive and inferential. The results of the study concluded that the tolerant attitude of students in the high category is 80.9%. The level of religiosity of students in the high category is 75.5%, while the level of religiosity of students in the high category is 57.7% of the number of respondents as many as 503. The relationship between religiosity and multiculturalism with tolerance is in the high category. with r=0.773 with p. 0.00. Those who are obedient to worship, understand religion correctly and respect differences in culture, religion, and customs, apparently tend to be more tolerant.